Litter-Induced Reduction in Ecosystem Multifunctionality Is Mediated by Plant Diversity and Cover in an Alpine Meadow - Ma, Zhouwen; Wu, Jing; Li, Lan; Zhou, Qingping; Hou, Fujiang (Frontiers in Plant Science, 2021)
Litter has been shown to alter the structure and functions of grassland ecosystems, and a knowledge of the effects of litter is essential for understanding the dynamics of ecosystem multifunctionality. However, relatively little is known about the effects of plant litter on ecosystem multifunctionality in alpine meadows. A three-year field experiment was conducted to explore how litter manipulation affects ecosystem multifunctionality. The plant litter treatments that were applied consisted of a range of litter mass levels and three dominant plant species, in an alpine meadow on the Qinghai-Tibet Plateau (QTP). The results showed that litter mass manipulation had a negative effect on ecosystem multifunctionality and most individual ecosystem functions (species richness, plant cover and above-ground biomass), but had a positive effect on plant functional group evenness. In particular, the study found that low or medium amounts of litter (≤ 200 g m-2) were beneficial in maintaining a high level of ecosystem multifunctionality. Furthermore, a structural equation model revealed that ecosystem multifunctionality was driven by indirect effects of litter mass manipulation on plant functional group evenness, plant cover and species richness. These results suggest that litter-induced effects may be a major factor in determining grassland ecosystem multifunctionality, and they indicate the potential importance of grassland management strategies that regulate the dynamics of litter accumulation.